Different Screening Definitions have Little Impact on Polypectomy Rate Estimates - Mengzhu Jiang; Maida J Sewitch; Lawrence Joseph; Alan N Barkun (Canadian Journal of Gastroenterology)
BACKGROUND: Polypectomy rate is a surrogate quality indicator for screening colonoscopy. Various methods for identifying screening colonoscopies have been used and it is unclear how different definitions affect the estimated polypectomy rate.